Well basically if they lost 8 points and gained 6, they have -2 points.
the answer 11
Step-by-step explanation:
6+16=22
22÷2=11
Answer:
Options (1), (2), (3) and (7)
Step-by-step explanation:
Given expression is
.
Now we will solve this expression with the help of law of exponents.
![\frac{\sqrt[3]{8^{\frac{1}{3}}\times 3} }{3\times2^{\frac{1}{9}}}=\frac{\sqrt[3]{(2^3)^{\frac{1}{3}}\times 3} }{3\times2^{\frac{1}{9}}}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%5B3%5D%7B8%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%5Ctimes%203%7D%20%7D%7B3%5Ctimes2%5E%7B%5Cfrac%7B1%7D%7B9%7D%7D%7D%3D%5Cfrac%7B%5Csqrt%5B3%5D%7B%282%5E3%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%5Ctimes%203%7D%20%7D%7B3%5Ctimes2%5E%7B%5Cfrac%7B1%7D%7B9%7D%7D%7D)
![=\frac{\sqrt[3]{2\times 3} }{3\times2^{\frac{1}{9}}}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B%5Csqrt%5B3%5D%7B2%5Ctimes%203%7D%20%7D%7B3%5Ctimes2%5E%7B%5Cfrac%7B1%7D%7B9%7D%7D%7D)
![=\frac{2^{\frac{1}{3}}\times 3^{\frac{1}{3}}}{3\times 2^{\frac{1}{9}}}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B2%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%5Ctimes%203%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%7D%7B3%5Ctimes%202%5E%7B%5Cfrac%7B1%7D%7B9%7D%7D%7D)
![=2^{\frac{1}{3}}\times 3^{\frac{1}{3}}\times 2^{-\frac{1}{9}}\times 3^{-1}](https://tex.z-dn.net/?f=%3D2%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%5Ctimes%203%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%5Ctimes%202%5E%7B-%5Cfrac%7B1%7D%7B9%7D%7D%5Ctimes%203%5E%7B-1%7D)
![=2^{\frac{1}{3}-\frac{1}{9}}\times 3^{\frac{1}{3}-1}](https://tex.z-dn.net/?f=%3D2%5E%7B%5Cfrac%7B1%7D%7B3%7D-%5Cfrac%7B1%7D%7B9%7D%7D%5Ctimes%203%5E%7B%5Cfrac%7B1%7D%7B3%7D-1%7D)
![=2^{\frac{3-1}{9}}\times 3^{\frac{1-3}{3}}](https://tex.z-dn.net/?f=%3D2%5E%7B%5Cfrac%7B3-1%7D%7B9%7D%7D%5Ctimes%203%5E%7B%5Cfrac%7B1-3%7D%7B3%7D%7D)
[Option 2]
[Option 1]
![2^{\frac{2}{9}}\times 3^{-\frac{2}{3} }=(\sqrt[9]{2})^2\times (\sqrt[3]{\frac{1}{3} } )^2](https://tex.z-dn.net/?f=2%5E%7B%5Cfrac%7B2%7D%7B9%7D%7D%5Ctimes%203%5E%7B-%5Cfrac%7B2%7D%7B3%7D%20%7D%3D%28%5Csqrt%5B9%5D%7B2%7D%29%5E2%5Ctimes%20%28%5Csqrt%5B3%5D%7B%5Cfrac%7B1%7D%7B3%7D%20%7D%20%29%5E2)
![=(2^2)^{\frac{1}{9}}\times (3^2)^{-\frac{1}{3} }](https://tex.z-dn.net/?f=%3D%282%5E2%29%5E%7B%5Cfrac%7B1%7D%7B9%7D%7D%5Ctimes%20%283%5E2%29%5E%7B-%5Cfrac%7B1%7D%7B3%7D%20%7D)
[Option 3]
![2^{\frac{2}{9}}\times 3^{-\frac{2}{3} }=(2^2)^{\frac{1}{9}}\times (3^{-2})^{\frac{1}{3} }](https://tex.z-dn.net/?f=2%5E%7B%5Cfrac%7B2%7D%7B9%7D%7D%5Ctimes%203%5E%7B-%5Cfrac%7B2%7D%7B3%7D%20%7D%3D%282%5E2%29%5E%7B%5Cfrac%7B1%7D%7B9%7D%7D%5Ctimes%20%283%5E%7B-2%7D%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%20%7D)
[Option 7]
Therefore, Options (1), (2), (3) and (7) are the correct options.
<span>Simplifying
2x + 18y = 36
Solving
2x + 18y = 36
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-18y' to each side of the equation.
2x + 18y + -18y = 36 + -18y
Combine like terms: 18y + -18y = 0
2x + 0 = 36 + -18y
2x = 36 + -18y
Divide each side by '2'.
x = 18 + -9y
Simplifying
x = 18 + -9y</span>
3 are expected to have the condition.
The expected value is the found by multiplying the probability by the number in the sample:
(1/200)×600
= (1/200)×(600/1)
= (1×600)/(200×1)
= 600/200 = 3